2018
DOI: 10.4067/s0718-58392018000300438
|View full text |Cite
|
Sign up to set email alerts
|

Effect of abscisic acid and methyl jasmonate preharvest applications on fruit quality and cracking tolerance of sweet cherry

Abstract: Rain-induced cherry fruit cracking is one of the most important problems in the cherry industry, and its occurrence causes significant economic losses. Sweet cherry (Prunus avium [L.] L.) is a non-climacteric fruit affected by both abscisic acid (ABA) and methyl jasmonate (MeJA) during development. The objective of this study was to evaluate the effect of these phytohormones on cracking susceptibility and quality parameters of sweet cherry fruit ('Bing'), located in the central region of Chile. During two seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 40 publications
6
45
2
Order By: Relevance
“…In our current study, it is worth pointing out that exogenous NO or ABA treatment was effective in reducing CI and delaying peach fruit softening. Similar results have been found in other cold‐sensitive fruits such as Hami melon, papaya, zucchini and sweet cherry . SSC and peel color are essential factors affecting fruit flavor and appearance and can be affected by fruit senescence.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In our current study, it is worth pointing out that exogenous NO or ABA treatment was effective in reducing CI and delaying peach fruit softening. Similar results have been found in other cold‐sensitive fruits such as Hami melon, papaya, zucchini and sweet cherry . SSC and peel color are essential factors affecting fruit flavor and appearance and can be affected by fruit senescence.…”
Section: Discussionsupporting
confidence: 83%
“…Similar results have been found in other cold-sensitive fruits such as Hami melon, 35 papaya, 34 zucchini 15 and sweet cherry. 21 SSC and peel color are essential factors affecting fruit flavor and appearance and can be affected by fruit senescence. In this study, SSC in peach fruit increased, peaking on the fourth week and then decreased gradually over time during cold storage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cherry cracking incidence did not significantly decrease with spray treatments in both years, it was observed that also the AN-and ABA-treated fruits showed the least cracking index in 2015 and 2016 ( Figure 5). Reduced cracking index for ABA-treated 'Bing' cherry was reported by Balbontín et al [25]. An additional promising strategy to mitigate cherry cracking is AN, as had been reported by our research group for 'Skeena' and 'Sweetheart' cherry fruits [31].…”
Section: Effect Of Spray Treatments On Yield Of Sweet Cherry Trees Ansupporting
confidence: 78%
“…Kaolin sprays on navel orange in this experiment has delayed the ripening processes of orange and these results are in accordance with the work of on Balady mandarin and also are supported by the results of Maletiska et al (2015) on clingstone peach displaying a higher value of firmness for kaolin treated fruits compared to control. Balbontín et al (2018) concluded that application methyl Jasmonate on sweet cherry increased firmness of fruits indicating that Jasmonic acid influences physiological processes of ripening by delaying softening as it is involved in the regulation of cell wall metabolism genes.…”
Section: Physical Characteristicsmentioning
confidence: 99%